(untitled) (International Journal of Innovative Research in Engineering & Management, 2021)
In the last five decades, the value of English has grown to a new height owing to the change in the mode of our business. The globe has shrunken to a small village in which businesses are carried out across different time zones and spaces in the virtual world. In such a small world with multiple business networks, English stands out as the most important lingua franca. The language has achieved the stature of a world lingua franca as the numbers of non-native speakers are growing in numbers. In such context, English becomes an important language for the professional students who aspire to become a successful professional in his/her own right. Aligning with the need of the students, the teachers and practitioners of English Language Teaching, work tirelessly to meet the needs and requirements of the students. This paper attempts to present the various approaches and methodologies of teaching English to the students of Engineering and Management in order to develop their communication skills in English.